Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan - Dery Wijaya; Samsuri Samsuri; Rachmat Gunawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Performance is a very important part to achieve the goals of a company. Given the magnitude of the influence of leadership style and organizational culture on employee performance. This study aims to determine the effect of leadership style and organizational culture on employee performance at Mega Hotel & Resort. The method used is multiple linear regression analysis. The total sample of all employees of Hotel Mega & Resort is 55 people. The results of the study simultaneously show that the variables of leadership style and organizational culture as a whole have a positive and significant effect on employee performance. Partially, the variables of leadership style and organizational culture have a positive and significant influence